2016
DOI: 10.1017/langcog.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating time in space: the structure and function of space–motion metaphors of time

Abstract: This paper studies the principles according to which spatial and motion concepts metaphorically structure temporal concepts in some languages. There are two types of space–motion metaphor of time, distinguished by whether or not the metaphor is structured by a person’s perspective. “Christmas is approaching” and “We are approaching Christmas” are perspectival. “New Year’s follows Christmas” is not. This contrast in deixis and frame of reference is linguistically relevant whether the contrast has to do with ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Across many languages and cultures, there is a pervasive tendency for time to be represented in terms of space (Evans, ; Haspelmath, ; Moore, ; Núñez & Cooperrider, ; Stocker, Hartmann, Martarelli, & Mast, ). While there are various types of spatial metaphors for time, most attention in the literature has been paid to the mappings between front‐back axis and time (e.g., Boroditsky, ; Clark, ; Duffy, Feist, & McCarthy, ; Lakoff & Johnson, ; Moore, ; to name just a few). Research has revealed that there are systematic differences in space‐mappings in different languages.…”
Section: Introductionmentioning
confidence: 99%
“…Across many languages and cultures, there is a pervasive tendency for time to be represented in terms of space (Evans, ; Haspelmath, ; Moore, ; Núñez & Cooperrider, ; Stocker, Hartmann, Martarelli, & Mast, ). While there are various types of spatial metaphors for time, most attention in the literature has been paid to the mappings between front‐back axis and time (e.g., Boroditsky, ; Clark, ; Duffy, Feist, & McCarthy, ; Lakoff & Johnson, ; Moore, ; to name just a few). Research has revealed that there are systematic differences in space‐mappings in different languages.…”
Section: Introductionmentioning
confidence: 99%
“…First, those two dominant patterns reflect the influence of the spatial expressions of time in the language that the participants spoke. Cross-lingual studies have shown that many languages use spatial metaphors to express time in the spatial reference frame ( Moore, 2011 , 2017 ; Tenbrink, 2011 ; Brown, 2012 ). Moore (2011) has suggested that the Japanese word “mae,” which means “front” in English, is used to describe an earlier time in a temporal sequence from the field-based reference frame and to describe the future from the egocentric reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual metaphor “TIME IS SPACE” is considered as a deep metaphor for all human being ( Lakoff and Johnson, 1999 , p. 139; Fauconnier and Turner, 2008 , p. 56). Scholars have provided plentiful evidences from the following three aspects: (1) Evidence from languages and cultural artifacts ( Clark, 1973 ; Traugott, 1978 ; Tversky et al, 1991 ; Haspelmath, 1997 ; Evans, 2003 , 2005 , 2013a , 2013b ; Levinson, 2003 ; Moore, 2006 , 2011 , 2014a , b , 2017 ; Boroditsky and Gaby, 2010 ; Fuhrman et al, 2011 ; Radden, 2011 ; Tenbrink, 2011 ; Núñez and Cooperrider, 2013 ; Pamies-Bertrán and Yuan, 2020 ); (2) Evidence from co-speech gesture or other non-linguistic thought ( Casasanto and Lozano, 2006 ; Núnez and Sweetser, 2006 ; Cooperrider and Núñez, 2009 ; Casasanto, 2010 , 2016 ; Fuhrman and Boroditsky, 2010 ; Casasanto and Jasmin, 2012 ; Levinson and Majid, 2013 ; Bender and Beller, 2014 ; Cooperrider et al, 2014 ; Walker and Cooperrider, 2016 ; Li, 2017 ); (3) Evidence from private mental representations ( Boroditsky, 2000 ; Boroditsky and Ramscar, 2002 ; Kemmerer, 2005 ; Núñez et al, 2006 ; Casasanto and Boroditsky, 2008 ; Margolies and Elizabeth, 2008 ; Ding et al, 2020 ).…”
Section: Spatial-time Conceptualization and Eventive-time Conceptuali...mentioning
confidence: 99%